2023
DOI: 10.1007/s12010-023-04317-z
|View full text |Cite
|
Sign up to set email alerts
|

Substrates of Opposite Polarities and Downstream Processing for Efficient Production of the Biosurfactant Mannosylerythritol Lipids from Moesziomyces spp.

Abstract: Biosurfactants can replace fossil-driven surfactants with positive environmental impacts, owing to their low eco-toxicity and high biodegradability. However, their large-scale production and application are restricted by high production costs. Such costs can be reduced using renewable raw materials and facilitated downstream processing. Here, a novel strategy for mannosylerythritol lipid (MEL) production explores the combination of hydrophilic and hydrophobic carbon sources sideways with a novel downstream pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Therefore, consequent research was aimed at the production of MELs from waste streams containing high concentrations of simple sugars rather than ones requiring pretreatment. respectively (Faria et al, 2023). These studies showed the potential of utilizing a combination of hydrophobic and hydrophilic waste streams to achieve enhanced microbial MEL production.…”
Section: Utilizing Industrial Waste Streams For the Production Of Melsmentioning
confidence: 84%
See 2 more Smart Citations
“…Therefore, consequent research was aimed at the production of MELs from waste streams containing high concentrations of simple sugars rather than ones requiring pretreatment. respectively (Faria et al, 2023). These studies showed the potential of utilizing a combination of hydrophobic and hydrophilic waste streams to achieve enhanced microbial MEL production.…”
Section: Utilizing Industrial Waste Streams For the Production Of Melsmentioning
confidence: 84%
“…Similarly, Faria et al (2023) investigated the production of MELs by P. antarctica PYCC 5048 and P. aphidis PYCC 5535, initially grown on 40 g/L glucose before being supplemented with 20 g/L waste cooking oil. It was found that P. antarctica PYCC 5048 and P. aphidis PYCC 5535 achieved competitive MEL titers of 12.6 and 10 g/L, respectively (Faria et al, 2023). These studies showed the potential of utilizing a combination of hydrophobic and hydrophilic waste streams to achieve enhanced microbial MEL production.…”
Section: Production Of Melsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent study by Faria et al (2023) [29] showed an alternative strategy, designed to reach both sufficient MEL titres and high purity by co-feeding the microorganisms carbon sources with opposite polarities (glucose and soybean oil). This study explored the carbon equimolar substitution of part of the oil with a hydrophilic carbon source (D-glucose).…”
Section: Mannosylerythritol Lipids: Structure Properties and Productionmentioning
confidence: 99%
“…Between fermentation and final application, there is a very important step, which is the MEL's separation from the fermentation broth and subsequent purification. For this purpose, the most common techniques are liquid-liquid extraction and column chromatography, but other techniques such as membrane filtration [29,31], heat exposure and decantation [32], and separation of MEL beads with integrated devices [33] are being explored.…”
Section: Mannosylerythritol Lipids: Structure Properties and Productionmentioning
confidence: 99%